Current progress of ferroptosis study in ovarian cancer - Tan, Zhuomin; Huang, Hui; Sun, Wenyan; Li, Ya; Jia, Yinnong (Frontiers in Molecular Biosciences, 2022)
Tumors are the leading cause of death in every country around the world, with ovarian cancer ranks the third among gynecological malignancies. Ovarian cancer treatment is likely to develop chemotherapy resistance and high recurrence rate. Ferroptosis is a massive iron-dependent accumulation of lipid reactive oxygen species. With the in-depth study of ferroptosis, its associated mechanism with tumor is gradually elucidated, which will enhance the involvement of ferroptosis in ovarian cancer. This review focus on the current development of ferroptosis, regulation mechanism, and progress in ovarian cancer research.